Oxidized low-density lipoproteins stimulate adhesion of monocytes to endothelial cells - Niu Xi-Lin; Yan Xiang-Dong; Guo Zhao-Gui (Acta Pharmacologica Sinica, 2016)
AIM: To study the effects of oxidized low-density lipoproteins (ox-LDL) on the adhesiveness of monocytes to endothelial cells. METHODS: LDL was obtained from healthy human plasma by ultracentrifugation, and oxidized by CuSO4 10 mumol.L-1. The assay of adhesion was performed using cultured bovine aortic endothelial cells (BAEC) and human peripheral blood monocytes. RESULTS: Pretreatment BAEC with ox-LDL enhanced monocyte adhesion to BAEC in time- and dose-dependent manner. ox-LDL as little as 10 mg.L-1 and 30 min of preincubation stimulated monocyte adhesion. Cycloheximide (Cyc, a protein synthesis inhibitor) 1 mg.L-1 and staurosporine (Sta, a PKC inhibitor) 20 nmol.L-1 abolished the effect of ox-LDL (60 mg.L-1), but dextran sulfate 20 mg.L-1 had no effect on monocyte adhesion. Phorbol 12-myristate 13-acetate (PMA) 1 nmol.L-1 and lysophosphatidylcholine (Lys) 6 mumol.L-1 mimicked the effects of ox-LDL and potentiated monocyte adhesion. Sta also suppressed the augmentative effects of Lys and PMA. CONCLUSION: ox-LDL enhances the adhesion of monocytes to BAEC through the activation of PKC.